"Orofacial Dystonia—A Silent Killer": Mandibular Fractures with Orofacial Dystonia, A Report of a Case and Review. (27th January 2021) - Shukla, Anand deep; Srikanth, G.; Chitra, A.; Singh, Anupam; Nayak, Sunil
Abstract : Mandibular parasymphysis fracture is very commonly observed especially in old age when there is resorptions of the alveolar ridges. In cervical dystonia, there is centrally mediated disease in which there is uncontrolled and spasmodic contraction of the facial and the masticatory muscles. Due to the application of this sudden and uncontrolled force, there is a tendency of the bone to unfavourably remodel and weaken. The case presented here is of a geriatric patient who presented to us with a fracture at the right parasymphysis and left dentoalveolar region of the mandible and was suffering from cervical dystonia. Management of this case posed a challenge in every step, and it needed a resurgery where the fracture was managed by the placement of reconstruction plate. Not many cases in the literature have been reported where dystonic movements have resulted in the fracture of the mandible.